Magnetization process in a frustrated plaquette dimer - Elias, F. (2017)
The magnetic phase diagram of a plaquette dimerized and frustrated antiferromagnetic ladder system is studied by using a combination of numerical and analytical techniques. For the strongly frustrated regime, series expansions and bond operator techniques are employed to analyze zero magnetic field, whereas low-energy effective models are used to study the complete magnetization process. The interplay between frustration and dimerization gives rise to a rich plateau structure that is captured by effective models and corroborated by numerical density matrix renormalization group simulations, in particular, the emergence of intermediate plateaus at M=14 and 34 of saturation in the magnetization curve is clarified.